A Rasch analysis of the lumbar spine instability questionnaire. (3rd July 2021) - Macedo, Luciana Gazzi; Kuspinar, Ayse; Roduta Roberts, Mary; Maher, Chris G.
ABSTRACT: Purpose : A 2014 study found that the Lumbar Spine Instability questionnaire predicts response to two different types of exercise therapy. This is the first decision tool that has predicted response to exercise for chronic low back pain. The objective of this study was to evaluate the Lumbar Spine Instability questionnaire using Rasch analysis. Methods : Baseline data from patients included in a randomized controlled trial with chronic non-specific low back pain were included. Rasch Measurement Theory was used to assess the ordering of items along a common scale, data-to-model fit, Person Separation Index, unidimensionality and Differential Item Functioning. Results : Responses from 172 patients (102 females) underwent Rasch analysis. All Lumbar Spine Instability questionnaire items had fit residuals between ± 2.5 and Chi-Square values were non-significant with Bonferroni corrections. The Lumbar Spine Instability questionnaire demonstrated a Person Separation Index of 0.64, which is below the recommended cut-off of 0.7. Differential Item Functioning by different pain levels was identified for one item. Conclusion : The Lumbar Spine Instability questionnaire was found to be unidimensional, suggesting that the use of a summary score is appropriate. However, the low Person Separation Index value suggests that more items may be needed to increase the questionnaire's ability to discriminate among individuals with high and low clinical instability.